SUSTAINABLE AGRICULTURE UTILIZATION IN MAINTAINING BIODIVERSITY AND PLANT PRODUCTIVITY IN BATU BAJANJANG VILLAGE - Azmen Kahar; Hermansyah; Khairani Saladin; Vischa Mansyera Pratama; Anggun Kurniati; Jefriyan Putra Deska; Muhammad Althof Fauzan Zain; Nasywa Farhanah Izan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This study examines the implementation of sustainable agriculture in Nagari Batu Bajanjang, focusing on efforts to maintain biodiversity and increase crop productivity. Nagari Batu Bajanjang has great potential in agricultural development. This study analyzes the transformation from a conventional agricultural system that still relies on monoculture practices and the use of chemicals, to a sustainable agricultural system. The implementation of sustainable agriculture is carried out through several main strategies, including crop diversification, the application of an agroforestry system, the use of organic fertilizers, and the development of a modern irrigation system. The results of the study indicate that the implementation of sustainable agriculture has a positive impact in three main aspects: increasing biodiversity, improving long-term land productivity, and increasing farmer income. The success of this implementation requires active collaboration between local governments, research institutions, and local farmer communities.